Trade-off of major bleeding versus myocardial infarction on mortality after percutaneous coronary intervention. Issue 1 (11th January 2022) - Ng, Andrew Kei-Yan; Ng, Pauline Yeung; Ip, April; Lam, Lap Tin; Siu, Chung-Wah
Abstract : Background: The choice of antithrombotic therapy after percutaneous coronary intervention (PCI) is heavily dependent on the relative trade-off between major bleeding (MB) and myocardial infarction (MI). However, the mortality trade-off was mostly described in Western populations and remained unknown in East Asians. Method: This was a retrospective cohort study from 14 hospitals under the Hospital Authority of Hong Kong between 2004 and 2017. Participants were patients undergoing first-time PCI and survived for the first year. Patients were stratified by the presence of MB and MI during the first year. The primary endpoint was all-cause mortality between 1 and 5 years after PCI. The secondary endpoint was cardiovascular mortality. Results: A total of 32 180 patients were analysed. After adjustment for baseline characteristics and using patients with neither events as reference, the risks of all-cause mortality were increased in patients with MI only (HR, 1.63; 95% CI 1.45 to 1.84; p<0.001), further increased in those with MB only (HR, 2.11, 95% CI 1.86 to 2.39; p<0.001) and highest in those with both (HR, 2.92; 95% CI 2.39 to 3.56; p<0.001). In both Cox regression and propensity score analyses, MB had a stronger impact on all-cause mortality than MI, but similar impact on cardiovascular mortality. Conclusions: Both MB and MI within the first year after PCI were associated with increase in all-cause and cardiovascular mortality in Chinese patients, but the impact was stronger with MB.